Impulsive action: emotional impulses and their control - Frijda, Nico H.; Ridderinkhof, K. Richard; Rietveld, Erik (Frontiers in Psychology, 2014)
This paper presents a novel theoretical view on impulsive action, integrating thus far separate perspectives on nonreflective action, motivation, emotion regulation, and impulse control. We frame impulsive action in terms of directedness of the individual organism towards, away, or against other givens – towards future states and away from one's present state. First, appraisal of a perceived or thought-of event or object on occasion, rapidly and without premonition or conscious deliberation, triggers a motive to modify one's relation to that event or object. Situational specifics of the event as perceived and appraised motivate and guide selection of readiness for a particular kind of purposive action. Second, perception of complex situations can give rise to multiple appraisals, multiple motives, and multiple simultaneous changes in action readiness. Multiple states of action readiness may interact in generating action, by reinforcing or attenuating each other, thereby yielding impulse control. We show how emotion control can itself result from a motive state, or state of action readiness. Our view links impulsive action mechanistically to states of action readiness, which is the central feature of what distinguishes one kind of emotion from another. It thus provides a novel theoretical perspective to the somewhat fragmented literature on impulsive action.